Uji Efektivitas Ekstrak Daun Salam (Syzygium polyanthum) sebagai Repellent Semprot terhadap Kecoa (Periplaneta americana) - Rio Purnama (IKesT Muhammadiyah Palembang, 2025)
Introduction: Vector-borne diseases caused by cockroaches (Periplaneta americana) are still a health concern in Indonesia. Cockroaches can transmit diseases like diarrhea and typhoid fever. Bay leaf (Syzygium polyanthum) contains active compounds such as flavonoids, tannins, essential oils, and alkaloids, which are disliked by cockroaches. Method: This study applied a true experimental design with 5%, 10%, and 15% bay leaf extract concentrations. The test subjects were Periplaneta americana. Data analysis was conducted using univariate and bivariate methods (ANOVA test). Results: The 15% concentration repelled an average of 9.33 cockroaches. ANOVA test showed a significant p-value of 0.005 (p < 0.05), indicating a significant effect of extract concentration on cockroach repellency. Conclusion: Bay leaf extract is effective as a natural repellent against cockroaches, with 15% concentration being the most effective.